2018
DOI: 10.1523/jneurosci.1995-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms for Adaptive Learned Avoidance of Mental Effort

Abstract: Humans tend to avoid mental effort. Previous studies have demonstrated this tendency using various demand-selection tasks; participants generally avoid options associated with higher cognitive demand. However, it remains unclear whether humans avoid mental effort adaptively in uncertain and non-stationary environments, and if so, what neural mechanisms underlie this learned avoidance and whether they remain the same irrespective of cognitive-demand types. We addressed these issues by developing novel demand-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…Earlier studies have shown valuation regions encoding reward signals modulated by prior or anticipated cognitive demands (Botvinick et al, 2009;Satterthwaite et al, 2012;Schmidt et al, 2012;Schouppe et al, 2014a;Vassena et al, 2014;Dobryakova et al, 2017;Nagase et al, 2018). These results imply that the valuation network should also encode SV during cognitive effortbased decision-making.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Earlier studies have shown valuation regions encoding reward signals modulated by prior or anticipated cognitive demands (Botvinick et al, 2009;Satterthwaite et al, 2012;Schmidt et al, 2012;Schouppe et al, 2014a;Vassena et al, 2014;Dobryakova et al, 2017;Nagase et al, 2018). These results imply that the valuation network should also encode SV during cognitive effortbased decision-making.…”
Section: Discussionmentioning
confidence: 66%
“…This could reflect limited power to detect reward encoding: the dACC has elsewhere been shown to track both physical effort costs and reward amount (Harris and Lim, 2016;Klein-Flügge et al, 2016). Interestingly, however, numerous lines of evidence also suggest a somewhat more specialized role for these regions in processing cognitive effort costs including involvement in control modulation (Dosenbach et al, 2006), error awareness and processing (Klein et al, 2007), decisionmaking about physical effort (Croxson et al, 2009;Prévost et al, 2010;Kennerley et al, 2011;Kurniawan et al, 2013;Skvortsova et al, 2014), self-reported cognitive effort (in the AI; Otto et al, 2014), and learning about cognitive effort costs (Botvinick, 2007;Nagase et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that putative valuation regions reflect modulation of reward signals as a function of prior cognitive load, for example, or of incentive cues as a function of anticipated cognitive demands (Botvinick et al, 2009;Dobryakova et al, 2017;Nagase et al, 2018;Satterthwaite et al, 2012;Schmidt et al, 2012;Schouppe et al, 2014a;Vassena et al, 2014). These prior results imply that the domain-general valuation network should also encode SV during cognitive effort-based decision-making.…”
Section: Discussionmentioning
confidence: 86%
“…Also, unit recordings of monkey ACC neurons engaged in physical effort-based decision-making involves opposing signs in neighboring cells processing cost and benefit information (Kennerley et al, 2011) indicating that particular cost or benefit signals may cancel out at the resolution of fMRI. Interestingly, however, numerous lines of evidence also suggest a somewhat more specialized role for these regions in processing cognitive effort costs including their involvement in cognitive task attention and control modulation (Dosenbach et al, 2006), error awareness and processing (Klein et al, 2007), processing of affectively negative stimuli (Duerden et al, 2013), decision-making and learning about physical effort costs (Croxson et al, 2009;Kennerley et al, 2011;Kurniawan et al, 2013;Prévost et al, 2010;Skvortsova et al, 2014), self-reported cognitive effort ratings, in the case of the AI (Otto et al, 2014), and perhaps most pointedly, learning about cognitive effort costs (Botvinick, 2007;Nagase et al, 2018). Our results are thus consistent with the overarching hypothesis that the dACC and AI specialize in processing effort cost information in the service of SV computation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain trial-by-trial estimates of efficacy and reward rate, we fitted a reinforcement learning model (Gläscher, Daw, Dayan, & O'Doherty, 2010;Sutton & Barto, 1998) to the continuous (range: 0-1) subjective estimates of efficacy and reward rate (cf. Eldar, Hauser, Dayan, & Dolan, 2016;Nagase et al, 2018;Rutledge et al, 2014). The model assumed that the estimate of efficacy for the next trial (Et+1) depended on the current efficacy feedback (Et) and the prediction error (δt) weighted by a constant learning rate (α):…”
Section: Learning Model and Statistical Analysesmentioning
confidence: 99%